Prevalence of Methicillin-Resistant Staphylococcus Species Among Filarial Lymphedema Patients in Ahanta West District of Ghana - Wireko, Solomon; Asiedu, Samuel Opoku; Kini, Priscilla; Aglomasa, Bill Clinton; Amewu, Emmanuel Kobla Atsu; Asiedu, Ebenezer; Osei-Akoto, Freda; Boahen, Kennedy Gyau; Obiri-Yeboah, Dorcas; Amato, Katherine Ryan; Kwarteng, Alexander (Frontiers in Tropical Diseases, 2021)
BACKGROUND Filarial pathologies such as lymphedema maybe associated with complications such as chronic non-healing wounds. Nonetheless, the role of bacteria population colonizing the lymphedematous legs have been posited to worsen the conditions of those living with the infection. These bacteria are usually comprised of staphylococcal species partly because they are commensals. Thus, this present study sought to type the Methicillin Resistant Staphylococcus aureus (MRSA) prevalence among individuals presenting with filarial lymphedema particularly as MRSA tends to affect treatments options. METHODS We recruited individuals (n=321) with stages I-VII of lymphedema in a cross-sectional study in the Ahanta West district of the Western Region of Ghana. Swabs from lymphedematous limb ulcers, pus and cutaneous surfaces were cultured using standard culture-based techniques. The culture isolates were later identified using MALDI-TOF Mass Spectrometry. RESULTS A total of 192 Staphylococci species were isolated with an overall prevalence of 39.7% (95% CI: 35% - 44%; N = 483). S. hominis was the most prevalent species (23.95%), followed by S. haemolyticus (20.83%), S. epidermidis (15.10%), S. aureus (10.41%) and S. saprophyticus (9.32%). The remaining 20.34% were distributed among S. wanneri, S. sciuri, S. pasteuri, S. xylosus, S. simulans, S. cohnii, S. caprae, S. lugdunensis, and S. capitis. Methicillin Resistant Staphylococcus aureus (MRSA), containing mecA gene, was detected in 21 out of 31 Staphylococci isolates tested, with an overall prevalence of 68% (95% CI: 51% - 84%). In addition, a virulent gene, Panton-Valentine Leucocidin (PVL), which is usually associated with S. aureus was detected in 20/31 (64.5%) S. aureus in the study. CONCLUSION These results suggest that MRSA species may pose a challenge to the treatment of filarial lymphedema with antibiotics particularly as doxycycline is currently being piloted in some endemic areas to treat the infection. Thus, intensive antimicrobial resistance surveillance should be conducted in endemic areas by Health Authorities to forestall the dilemma of multi-drug resistance not only against LF infection but other diseases.